2023
DOI: 10.1063/5.0118096
|View full text |Cite
|
Sign up to set email alerts
|

Free-electron–light interactions in nanophotonics

Abstract: When impinging on optical structures or passing in their vicinity, free electrons can spontaneously emit electromagnetic radiation, a phenomenon generally known as cathodoluminescence. Free-electron radiation comes in many guises: Cherenkov, transition, and Smith–Purcell radiation, but also electron scintillation, commonly referred to as incoherent cathodoluminescence. While those effects have been at the heart of many fundamental discoveries and technological developments in high-energy physics in the past ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 318 publications
0
18
0
Order By: Relevance
“…Free-electron radiation mainly includes Cherenkov radiation (CR), Smith–Purcell radiation (SPR), transition radiation (TR), etc. The schematics work well in the IR region and are shown in Figure for a clear demonstration, and the detailed interaction schematics are shown in Figures and .…”
Section: Light Emission and Modulation In 2d Structuresmentioning
confidence: 94%
See 1 more Smart Citation
“…Free-electron radiation mainly includes Cherenkov radiation (CR), Smith–Purcell radiation (SPR), transition radiation (TR), etc. The schematics work well in the IR region and are shown in Figure for a clear demonstration, and the detailed interaction schematics are shown in Figures and .…”
Section: Light Emission and Modulation In 2d Structuresmentioning
confidence: 94%
“…Free-electron radiation has found numerous applications in fields such as macroscopic electrodynamics, high-energy physics, biomedicine, and so on. Over the past decades, 2D materials have become an emerging platform for developing various nanophotonic devices and spurred intriguing discoveries combined with free-electron radiation. This section reviews the development of free-electron radiation based on 2D materials.…”
Section: Light Emission and Modulation In 2d Structuresmentioning
confidence: 99%
“…As opposed to bound-electron systems, free electrons are fundamentally versatile emitters (17)(18)(19)(20) that are dynamically tunable through their kinetic energy and can thus be tailored to any desired photonic wavelength, from the terahertz (21) to the x-ray (22) regimes. In the optical domain, free electron-light interactions (20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) enjoyed marked advancement in the past decade, demonstrating a plethora of quantum effects (27,34,35,37).…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to bound-electron systems, free electrons are fundamentally versatile emitters (17)(18)(19)(20) that are dynamically tunable through their kinetic energy and can thus be tailored to any desired photonic wavelength, from the terahertz (21) to the x-ray (22) regimes. In the optical domain, free electron-light interactions (20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) enjoyed marked advancement in the past decade, demonstrating a plethora of quantum effects (27,34,35,37). In the context of quantum photonics, it was shown that free electrons phase-matched to waveguide modes can excite multiple photonic quasiparticles with unity efficiency (29) and even herald the generation of photons in a room-temperature, integrated linear optical cavity (26,38).…”
Section: Introductionmentioning
confidence: 99%
“…The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/lpor.202200886 DOI: 10.1002/lpor.202200886 instead aiming to tailor advanced radiation characteristics such as spectralangular distribution, polarization, wavenumber, and phase. [10][11][12][13][14][15][16][17][18] For example, it is possible to generate effective Cherenkov radiation in both the forward and backward directions with a customizable radiation angle by utilizing the constructive interference of resonance transition radiation in photonic crystals. [19] The polarization of Smith-Purcell radiation can be tailored by utilizing metasurfaces or photonic flatband dispersions.…”
Section: Introductionmentioning
confidence: 99%